IMPLEMENTASI MEDIA FLASHCARD DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB MI AL-HIKMAH PAGAR ALAM KOTA - Yunatalia, Sela; Esha (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This research aims to improve student learning outcomes through the use of flashcard media. The lack of relevant learning media, which is applied during the teaching and learning process, causes low student scores in Arabic subjects in grade 1 of MI AI-Hikmah. Therefore, an interesting flascard media was applied to improve students' learning outcomes in Arabic vocabulary material. This research is a class action research (PTK). What was carried out at MI Al-hikmah Pagar Alam City, involved 21 students. With data collection techniques using observation, tests and documentation. The results of the study show that flascard media can improve students' learning outcomes in recognizing vocabulary in Arabic. Then based on the results of the tests that have been carried out, students' ability in Arabic vocabulary material is categorized to increase. With student learning outcomes carried out during the pre-cycle with an average score of 57.90%, Cycle I with an average score of 67.71%, and Cycle II with an average score of 80.33%.